P-154 Infliximab Infusions During Pregnancy: Are Pre-medications Safe and Effective in Preventing Infusion Reactions?. (February 2017) - Gold, Stephanie; Cohen-Mekelburg, Shirley; Shen, Nicole; Rupert, Amanda; Schneider, Yecheskel; Faggen, Alec; Steinlauf, Adam
Abstract : Background: Inflammatory bowel disease (IBD) is a chronic condition commonly diagnosed before or during prime reproductive years. While the majority of published literature suggests that most IBD-specific medications, including biologics such as infliximab, are safe to use, it is unknown if infliximab reactions are more or less common in pregnant women and whether premedications are either safe or effective in reducing infusion reactions. We sought to analyze infliximab infusions in the general IBD population and ultimately included pregnant women for a subgroup analysis in order to identify the frequency of reactions and the utility and safety of premedications in this unique patient cohort. Methods: A retrospective chart review was conducted including women with IBD who were treated with infliximab during pregnancy from 2008 to 2016. Baseline characteristics, included IBD-specific details, current medications, allergies and details of each infliximab infusion including the use of premedications and any reactions were collected. The outcome of each pregnancy included APGAR scores at birth. Results: Of 150 patients on infliximab identified, there were 20 pregnancies documented (19 singleton pregnancies and 1 set of twins). All subjects received infliximab prior to conception and continued their maintenance dose, which ranged from 5 to 10 mg/kg in 4 to 8 week intervals. Infusions were given over 2 hours. Infliximab was stopped in all patients at 32 to 34 weeks gestational age. Seventy percent (14/20) resumed infusions immediately following delivery, 25% (5/20) were lost to follow-up, and 5% (1/20) returned for re-induction 13 months later. Almost all, 95% (19/20), received pre medications, about half, 53% (10/19) received intravenous (IV) hydration (250 mL normal saline over 31 min) alone prior to the infliximab, while 26% (5/19) received oral diphenhydramine (25 mg). No infusion reactions occurred during pregnancy. The patient re-induced 13 months post-partum had an infusion reaction on the second and third re-induction doses despite pre-treatment with 50 mg IV diphenhydramine and 100 mg IV hydrocortisone. The pregnancy outcome was mostly live birth; 65% (13/20) within our institution and 20% (4/20) at an outside hospital. A minority of the patients had yet to deliver, 10% (2/20). One patient had a miscarriage at 9 weeks. For deliveries within our institution, APGAR scores at 1 and 5 minutes in 92% (12/13) of the live babies were 9 and 9 respectively and 8 and 9 on the remaining live birth. Conclusions: Premedications, including oral diphenhydramine or intravenous fluids were used in all but one of the pregnancies in this study and no harm to the newborns was seen. Although this study is small, it suggests that premedication use to prevent potentially serious infliximab reactions is safe and may be beneficial. To elucidate whether the low reaction rate was because of the premedications used (oral diphenhydramine or IV fluids) or whether it was from the natural tolerance to foreign material and suppression of the immune system in pregnancy, a future randomized controlled trial should be done.